Somalia : 2019 Article IV Consultation-Second Review Under the Staff-Monitored Program, and Request for New Staff-Monitored Program-Press Release; Staff Report; and Statement by the Executive Director for Somalia. (IMF Staff Country Reports; Country Report, 2019)
This paper discusses Somalia's 2019 Article IV Consultation, Second Review Under the Staff-Monitored Program (SMP), and Request for New SMP. Program implementation of SMP III has been strong, with all but one structural benchmark and all indicative targets met. The authorities have requested a new 15-month SMP to cement reforms and support reaching the Heavily Indebted Poor Country decision point as soon as the necessary conditions are met. The new national development plan will outline the authorities' priorities with respect to poverty reduction and inclusive growth. The consultation focused on policies to support higher and more inclusive growth, strengthen the medium-term fiscal framework, deepen the financial sector, increase economic resilience, and improve governance and the business environment. Discussions highlighted the need to implement a durable fiscal federal framework, establish a robust framework for effective natural resource management, and develop the medium-term fiscal framework. However, security and political risks, and climate shocks remain the main sources of risk.